2017
DOI: 10.1371/journal.pone.0175153
|View full text |Cite
|
Sign up to set email alerts
|

Th17 micro-milieu regulates NLRP1-dependent caspase-5 activity in skin autoinflammation

Abstract: IL-1β is a potent player in cutaneous inflammation and central for the development of a Th17 micro-milieu in autoinflammatory diseases including psoriasis. Its production is controlled at the transcriptional level and by subsequent posttranslational processing via inflammatory caspases. In this study, we detected inflammatory caspase-5 active in epidermal keratinocytes and in psoriatic skin lesions. Further, interferon-γ and interleukin-17A synergistically induced caspase-5 expression in cultured keratinocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 52 publications
0
33
1
2
Order By: Relevance
“…Although it was previously shown that the cleaved form of caspase 5 is present in lesional skin biopsy samples from psoriasis patients (Zwicker et al, 2017), we confirmed in a large number of lesional and nonlesional skin biopsy samples that cleaved forms of caspases 1, 4, and 5 are found in all lesional samples of tested psoriasis patients, whereas no cleaved forms are found in healthy donor samples. Moreover, cleaved forms of proinflammatory caspases were associated with an increase in the NLRP-3 and AIM-2 inflammasomes.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Although it was previously shown that the cleaved form of caspase 5 is present in lesional skin biopsy samples from psoriasis patients (Zwicker et al, 2017), we confirmed in a large number of lesional and nonlesional skin biopsy samples that cleaved forms of caspases 1, 4, and 5 are found in all lesional samples of tested psoriasis patients, whereas no cleaved forms are found in healthy donor samples. Moreover, cleaved forms of proinflammatory caspases were associated with an increase in the NLRP-3 and AIM-2 inflammasomes.…”
Section: Discussioncontrasting
confidence: 60%
“…In our study, we showed that keratinocytes cultured in conditions mimicking psoriasis (TNF-a þ IL-17A) are primed to secrete IL-1b in an inflammasome-dependent manner. Recently, it has been shown that the stimulation of keratinocytes with TNF-a alone or with IL-17A alone did not trigger caspase activation (Zwicker et al, 2017) but that the combination of at least two proinflammatory cytokines is necessary (Cho et al, 2012), suggesting that in the presence of several proinflammatory cytokines (IFN-g, TNF-a, IL-17, and IL-22), a strong increase in proinflammatory caspases could be obtained. This hypothesis is in agreement with what happens in psoriatic skin, where keratinocytes are in direct contact with a huge amount of proinflammatory cytokines secreted from the recruited immune cells and from themselves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current understanding of psoriasis pathogenesis involves dynamic networks of interrelated cells (immune cells, keratinocytes, peripheral nerves), receptors (TLRs, TRPV1, NaV 1.8) and molecules (chemokines, cytokines, proinflammatory mediators or even ds DNAs). Accelerated epidermopoiesis is the biological outcome of this pathological process.…”
mentioning
confidence: 99%